TATA KELOLA DAN SETATUS KEBERADAAN TATAH WAKAF DI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN LAMPUNG - Wagiyo Wagiyo; Asri Widya Putri; Putri Wulandari (FEB Institut Bakti Nusantara, 2022)
Waqf is one of the Islamic institutions that is closely related to the welfare of the people and has long been institutionalized in Indonesia, Waqf as the wealth of the Ummah belongs to the people, and the status of ownership and management must be carried out properly, so as to minimize risks such as; the risk of being taken back by the heirs after the waqf dies, the loss of the waqf due to the status of the waqf, the use of waqf that is not in accordance with its designation. This study uses a qualitative descriptive method which uses data sources through direct observations and interviews and questionnaires in the village, the Office of Religious Affairs in the Tataan Building District, and the Tataan Building District Office, Pesawaran Regency. The existence of waqf in 7 sub-districts in Pesawaran Regency, the number of waqf lands is 1,141 certified locations, 227 or those with certificate status only reached 19.89%, and 914 or 80.11% not yet certified. Meanwhile, for the 19 villages located in Gedong Tataan District, of the 176 locations the number of certified Waqf is only 26.14%, and those that have not been certified or 73.86%. The risk of possible claims from the waqf heirs is very large, so the risk of losing the waqf land is very large.